2016
DOI: 10.1136/jim-2015-000017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Challenge in Alzheimer's Disease: State of Knowledge and Future Needs

Abstract: A large body of experimental and postmortem findings indicate that Alzheimer's disease (AD) is associated with increased oxidative stress (OxS) levels in the brain. Despite the current limitations of OxS assessment in living subjects, recent data suggest that oxidative challenge might increase early both in the central nervous system and peripheral fluids. The aim of this review was to provide an overview of the existing literature linking systemic OxS to brain OxS in AD. We firmly believe that continued resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 163 publications
(427 reference statements)
3
93
1
Order By: Relevance
“…In the Italian subsample, COMT rs174696 was also associated with depression, partially supporting our hypothesis about oxidative stress. Indeed, COMT alterations may lead to an imbalance of monoamine levels (including serotonin) which, in turn, may lead to the development of a depressive phenotype, maybe through the increase of the oxidative stress [50]. However, this association was not replicated in our total sample or in the Greek subsample.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In the Italian subsample, COMT rs174696 was also associated with depression, partially supporting our hypothesis about oxidative stress. Indeed, COMT alterations may lead to an imbalance of monoamine levels (including serotonin) which, in turn, may lead to the development of a depressive phenotype, maybe through the increase of the oxidative stress [50]. However, this association was not replicated in our total sample or in the Greek subsample.…”
Section: Discussioncontrasting
confidence: 50%
“…Finally, our exploratory analysis on serologic parameters related to inflammation and oxidative stress processes (performed only in the Greek subsample) showed some nominal associations with the variants investigated. Taking into account that impairment of these 2 processes has been linked with both LOAD [50, 51] and depression [52, 53], this may point at a partial common genetic background between LOAD and depression [54]. Obviously, further studies are needed to confirm these hypotheses, particularly when considering the exploratory nature of these analyses.…”
Section: Discussionmentioning
confidence: 99%
“…151,152 Ab deposits and activated microglia and astrocytes are major sources of reactive oxygen species (ROS) in early AD. 153 Among the numerous harmful effects of ROS overproduction, mitochondrial dysfunction contributes to energy imbalance and apoptosis of nerve cells.…”
mentioning
confidence: 99%
“…There have been some reports of antioxidants showing some efficacy in few clinical trials, but these studies have not been able to answer whether antioxidants are truly protective against AD [78,79] . A randomized clinical trial has shown that treatment with α-tocopherol at a dose of 2000 IU/d reduces neuronal damage and slows the progression of AD in patients with moderately severe impairment [79,80] .…”
Section: Antioxidantsmentioning
confidence: 99%